SMART LEARNING: HOW AI HELPS STUDENTS LEARN LANGUAGES BETTER - Asliddinova Sabina Asliddin qizi (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
Artificial Intelligence (AI) is becoming a powerful tool in education, particularly in learning foreign languages. It offers personalized support, enhances motivation, and provides new ways to practice speaking, listening, and vocabulary. This article explores how AI tools are transforming the language learning process and helping students succeed.